Self-esteem and satisfaction with the chosen profession intechnical training students - Alania Contreras, Rubén Darío (2020)
Objective. To determine the relationship between self-esteem and satisfaction towards the chosen profession in Advertising Graphic Design students at the Instituto Superior Continental de Huancayo. Method. A study of basic type, correlational level and non-experimental, cross-sectional and descriptive correlational design, had a sample of 90 students to whom Coopersmith's self-esteem inventory (1997) and Vildoso's inventory of satisfaction with the chosen profession (2002) were applied. Results. It was found that self-esteem (v1 = 0.64) and satisfaction with the chosen profession (v2 = 3.51) are above the ideal average; the correlation between the study variables was direct, high (r = 0.61) and the significance was equally high (p = 0.00), so it was inferred that, greater self-esteem greater satisfaction with the chosen profession. Conclusion. There was a direct, high and high significance relationship between self-esteem and satisfaction towards the chosen profession in Advertising Graphic Design students at the Instituto Superior Continental de Huancayo.